New development: Local government ethics in England: how is local ownership working?. Issue 1 (2nd January 2017) - Doig, Alan
Abstract : With the abolition of the Audit Commission and the Standards Board for England, and the emphasis in the Localism Act 2011 on local ownership in England for standards, research was undertaken into a group of councils to assess their legislative compliance arrangements and the development of organizational ethical cultures. The research argues that the delivery of the former is a work-in-progress and that there is little evidence of the latter.